Use of real-time electronic extremity dosimeters for monitoring and optimisation of radiopharmacy technique - Cournane, S; McCavana, J; Maguire, D; Tutty, L; Harris, L; Lucey, J; Kenneally, C (Journal of radiological protection, 2024)
Radiopharmacy staff members are subject to extremity radiation doses, particularly to the fingertips. Dosemeters, such as, thermoluminescent detectors (TLDs) are currently used for monitoring fingertip doses. This study aimed to use real-time dosemeters to monitor radiopharmacy extremity doses to identify specific procedural steps associated with higher fingertip doses and, subsequently, reduce dose through promotion of optimised radiation protection practises. Five radiopharmacy operators were monitored using an ED3 active extremity dosemeter with a detector attached to each tip of the index fingers. Dose rate and accumulated dose data were matched to the handled radioactivity data, of 99m Tc-labelled radiopharmaceuticals only, with the dose per activity ( μ Sv MBq −1 ) calculated for each step. Once baseline dose data was established, an educational session identified technique adjustments toward improved radiation protection. A subsequent monitored session was undertaken with the dose data compared to quantify changes in operator doses. Radiopharmacy steps which significantly contributed to extremity doses were identified. The average accumulated dose per activity across all procedural steps for the 99m Tc-labelled radiopharmaceuticals for all operators before the educational session was 0.042 ± 0.045 μ Sv MBq −1 and 0.042 ± 0.041 μ Sv MBq −1 ( n = 89) for non-dominant and dominant index fingertips, respectively, and 0.030 ± 0.044 μ Sv MBq −1 and 0.031 ± 0.032 μ Sv MBq −1 ( n = 97), respectively, afterwards. Overall, there was an average 40.7% reduction in the total extremity dose received after the educational session. Real-time electronic extremity dosemeters for monitoring radiopharmacy extremity dose presented as a useful tool for incorporation into radiation protection education and training, towards optimised radiopharmacy technique.